The Role of TPD Pay Al Ma'ruf on Education of Orphans and Dhuafa Around The Al Ma'ruf Mosque - Tjoprajono, Nicolas Rahmat; Mardianto, Mardianto (Jurnal Basicedu, 2022)
The cost of education is a common problem for students, especially in the era of the Covid-19 pandemic. In addition, the free time that parents use to earn a living for the family during the Covid-19 pandemic has made a minimal role in social education and character guidance for children at home. For this reason, the role of the community is needed in helping to finance education and character building for underprivileged families. This study attempts to describe the role of the Al Ma'ruf Orphans Education Fund Management Team (TPD PAY) in the education of orphans and poor people around the al-Ma'ruf mosque. This type of research is based on a qualitative approach paradigm with a case study method. Data were obtained through interviews, observation, and document review. Then, it is analyzed through data sorting techniques, data presentation, and drawing conclusions. The results of this study indicate that the role of TPD PAY Al Ma'ruf for orphans and poor people around the al Ma'ruf mosque is very beneficial. This is marked by 3 aspects, namely (1) providing educational scholarships for orphans and poor people around the al Ma'ruf mosque, (2) fostering children's character based on the Koran, and (3) supporting children's talents and creativity.